Sensory appendage protein triggers alarm to pyrethroid in Indian malarial vector Anopheles culicifacies - Vaishali Saini; Pooja Rohilla; Vartika Srivastava; Gitanjali Tandon; Pooja Yadav; Nirmala Sankhala; Tanvi Singh; Gunjan Sharma; Suchi Tyagi; Tanwee Das De; Rajnikant Dixit (PLoS ONE, 2025)
Sensory appendage proteins (SAPs), members of the odorant-binding protein family, mediate chemical communication that is vital for mosquito survival and vector competence. Among the six identified SAP members, AcSAP1 and AcSAP2 exhibited dominant expression in olfactory and leg tissues of Anopheles culicifacies. Our findings reveal that the expression of AcSAP1, and to a lesser extent AcSAP2, is significantly modulated by the circadian rhythm, with peak expression coinciding with the nocturnal host-seeking behavior of female mosquitoes. A delayed host attraction response by the AcSAP1-silenced female mosquitoes accounts for AcSAP1’s potential role in host-seeking activities. In silico prediction data showed strong binding affinity to synthetic pyrethroid (deltamethrin); therefore, we tested the molecular responses of SAP to insecticide exposure. Strikingly, our WHO tube test bioassay-based experimental evaluation of mosquitoes’ survival and expression modulation in the olfactory, wings, and legs highlighted SAPs’ ability to sense toxic chemical cues. Finally, coupled with confocal microscopy analysis, our notable observation of a significant increase in AcSAP1 expression in the eyes of mosquitoes challenged with deltamethrin suggests a potential role in integrating visual and chemosensory cues. Our results highlight the multifaceted functions of SAPs, demonstrating their dual roles in host-seeking and insecticide avoidance, which have significant implications for understanding mosquito biology and developing novel vector control strategies.